Common bean entrepreneurial development in Sub-Saharan Africa - Nchanji, Eileen; Lutomia, Cosmas; Nyamolo, Victor (2024)
Entrepreneurship is pivotal for social and economic development, particularly in agri-food systems, where small and medium-scale enterprises, often women-led, face considerable challenges. This study explores the common bean value chain in six African countries—Cameroon, Kenya, Rwanda, Tanzania, Uganda, and Zambia—focusing on traders and processors. The methodology involved quantitative data collection from 23 common bean seed producers, traders, and processors through online and telephone interviews. Findings indicate women dominate bean processing, while men are prevalent in seed production and trading. Gender disparities are evident, with men-owned enterprises being larger and more operationally capable. Entrepreneurs typically rely on personal savings initially, with gendered differences in accessing start-up and expansion financing. Women-owned enterprises face greater challenges but demonstrate significant growth potential with improved access to financing. The study underscores the necessity for supportive environments to address gender disparities and foster entrepreneurship in the common bean value chain.